Correlation analysis of field-aligned currents from the magnetic measurements of GRACE follow-on mission - Chao Xiong (SpringerOpen, 2021)
Abstract In this study we performed a detailed analysis on the scale-size of field-aligned currents (FACs) at auroral latitudes, using the well-calibrated magnetic data from the non-dedicated magnetic field mission, Gravity Recovery and Climate Experiment Follow-On (GRACE-FO). With two spacecraft following each other, the GRACE-FO provides a good opportunity to identify the variation of FACs with different scale lengths. The results show that the auroral FACs can be classified into two groups: the small-scale ones, shorter than some tens of kilometers, dominated by kinetic Alfvén waves, are quite dynamic; and the large-scale ones, typically larger than 150 km, can be considered as quasi-static and persist longer than 1 min. The GRACE-FO observations also reveal that the small-scale FACs at the same location sometimes can persist over 25 s, e.g., around dusk and dawn hours, which is longer than the typical persistent period (10 s) of kinetic Alfvén waves as earlier reported. The FAC structures show clear magnetic local time dependence, with higher correlations between the spacecraft around dusk and dawn hours; lower correlations are found around midnight and lowest correlations around noon, implying that the small-scale FACs most frequently appear at the noon cusp region. Slightly better correlations of FACs between two spacecraft are found during local summer, and such seasonal dependence is dominated by the correlations of small-scale FACs at noon. However, further analysis shows that the small-scale FACs at noon have largest occurrence and intensity during local summer, which reveals that when interpreting the cross-correlation analysis the intensity of FACs needs to be taken into account. Graphical Abstract